Density of the blue-black urchin Echinotrix diadema (Linnaeus, 1758) in Tomini Bay, Indonesia - La Nane; Alfi Sahri R Baruadi; Herinda Mardin (Gorontalo State University, 2020)
The blue-black urchin has been widely known and utilized as food in the world, including Indonesia because sea urchin gonad can be consumed. However, the utilization of sea urchins in Gorontalo has not been performed. On the other hand, natural resources information is needed as the database for natural resources management in Tomini Bay. The aim of this study is to document the blue-black urchin Echinotrix diadema. This study conducted at Blue Marlin Beach, South Leato, Gorontalo, from November 2019 to December 2020. Sea urchin density was calculated with a 1 m × 1 m transect quadrate that positioned at interval 5 m in distance along 15 m of the transect line at the coral reef ecosystem. In parallel with the measurement of the density, sea urchin test diameter was measured with a Vernier caliper (0.01 mm accuracy), and the water temperature was measured with a thermometer. The results show that the average of sea urchin density is 3 ind. m–2 in November and December and 1 ind.m–2 in January. That density has no significant difference among the month. Moreover, the average size of the sea urchin test diameter is 60 mm in November, 63 mm in December, and 66 mm in January. The seawater temperature is 34 °C in November, 37 °C in December, and 33 °C in January. That results show that sea urchin density in the blue marlin beach is very low.